Evaluation of Bidikmisi scholarship program at state Islamic universities in Indonesia - Misra, Isra; Sadikin, Ali; Adlina, Fadiah (Graduate School, Universitas Negeri Yogyakarta in cooperation with Himpunan Evaluasi Pendidikan Indonesia (HEPI) Yogyakarta, 2022)
This study raised the theme of evaluating the Bidikmisi scholarship program at State Islamic Universities in Indonesia with the CIPP Model approach. The Bidikmisi scholarship program is the government's flagship program for outstanding students who are less able to meet the costs of higher education. This research is evaluation research focusing on four areas: context, input, process, and product evaluation. The research subjects were one managing director, three universities within the Ministry of Religion of the Republic of Indonesia, and 15 student informants who received the Bidikmisi scholarship. The results of the research on the evaluation of the Bidikmisi scholarship program show that (1) the context of the program is carried out in accordance with the technical instructions issued by the directorate of Islamic higher education related to the evaluation of the Bidikmisi scholarship program. (2) Evaluation of inputs is carried out by meeting the criteria considering starting from setting evaluation goals to the results of program evaluation, and program targets are high school graduates who have academic and non-academic achievements. (3) In the current process, the Bidikmisi scholarship program has been running for ten years with satisfactory results, and the selection is made openly and transparently. (4) The product of this program evaluation is policy improvement and service improvement to prospective scholarship recipients. The program manager must maintain its performance by improving program quality, achievement process, and control. Programs should focus on increasing resources by strengthening program recipients' academic skills and knowledge.